LEGAL PROTECTION FOR COMMUNITY HEALTH CENTERS THAT DO NOT HAVE PHARMACISTS IN PROVIDING PHARMACEUTICAL SERVICES - wahyuni, sri (Fakultas Hukum, Universitas Islam Bandung, 2023)
Puskesmas is a very important basic health care facility in Indonesia. One of the health services available at puskesmas is pharmaceutical services. The legal relationship between health workers who provide pharmaceutical services and patients in health centers is basically also a relationship born on the basis of a therapeutic agreement, which is an agreement where health workers who provide pharmaceutical services try their best to help the patient's recovery. The legal relationship between health workers who provide pharmaceutical services and patients in health centers is basically also a relationship born on the basis of a therapeutic agreement, which is an agreement where health workers who provide pharmaceutical services try their best to help the patient's recovery. However, often patients demand health workers both doctors and other health workers involved in their treatment in the Health Center because the disease is not successfully cured, even though in the therapeutic contract the object of the agreement is the best effort or effort of health workers be it doctors or other health workers to heal (inspanning verbitenis) and in no way cured or not cured of patients (resultaat verbitenis). The main problem is how legal protection for health centers that do not have pharmaceutical personnel in providing pharmaceutical services to patients is connected with Decree No. 74 of 2016 on Pharmaceutical Service Standards in Health Centers, and how the implementation of pharmaceutical services for health centers that do not have pharmaceutical personnel in practice in Sukadami Health Center